Identification of Ectoparasites and Endoparasites on Java Langurs (Trachypithecus sp.) and Silvery Gibbons (Hylobates moloch) in The Aspinall Foundation Indonesia Program - Ghifari Lutfi Fauzi; Endang Suprihati; Poedji Hastutiek; Boedi Setiawan; Retno Wulansari (Journal of Parasite Science (JoPS), 2021)
This study aimed to determine the prevalence rate and to identify parasites (endoparasite and ectoparasite) on Java Langur and Silvery Gibbon, these primates are rehabilitated in The Aspinall Foundation Indonesia Program. This research was conducted from February until October 2020. The fecal examination methods used in this research were native method and ovatec flotation method, while the ectoparasite examination used native method, mounting method, and scraping method. Based on a total of 68 samples examined, the result showed that 10 samples were positive infected by Trichuris trichiura and 2 samples were infested by Pedicinus ancoratus. The conclusion of this study indicated that the prevalence rate of Trichuris trichiura was 21.1% and Pedicinus ancoratus was 5.3% on 19 West Java Langurs, the prevalence rate of Trichuris trichiura was 3.3% and Pedicinus ancoratus was 3.3% on 30 East Java Langurs, the prevalence rate of Trichuris trichiura was 26.3% and no infestation of Pedicinus ancoratus was found on 19 Silvery Gibbons.